Assessment of Phenolic Contents and Antioxidant and Antibacterial Activities of Extracts from Four Varieties of Iranian Date Palm (Phoenix dactylifera L.) Seeds - Radfar, Ramin; Farhoodi, Mehdi; Ghasemi, Ismail; Mousavi Khaneghah, Amin; Shahraz, Farzaneh; Hosseini, Hedayat (Applied Food Biotechnology, 2019)
Background and objective: Every year, large quantities of date palm seeds are produced as byproducts in date processing and packaging industries, which is discarded or used as low-value materials for animal feeds and composts. However, these bioresources may include potentials to produce high-value added products in food industries. The major aim of the current study was to assess phenolic profiles and contents and antioxidant and antibacterial activities of four Iranian date palm seed extracts, namely Zahedi, Kabkab, Mazafati and Rabbi. Material and methods: Total phenolic contents, phenolic compounds profile and antioxidant and antibacterial activities of extracts from four Iranian date palm seeds were assessed using Folin-Ciocalteu, reversed-phase high-performance liquid chromatography, 2, 2-diphenyl-1picrylhydrazyl radical scavenging, agar disc diffusion and broth microdilution methods, respectively. Results and conclusion: Total phenolic contents varied 1480-3380 mg GAE 100 g-1 dw. cinnamic, chlorogenic, caffeic and 3, 5-dihydroxybenzoic acid included the primary phenolic compounds, respectively. Of the varieties, Kabkab and Mazafati seed extracts with IC50 values of 16.56 and 22.6 µg ml-1 demonstrated the highest and lowest radical scavenging activity, respectively. Results obtained from disc diffusion method revealed that all extracts included inhibitory effects against Staphylococcus aureus, but not against Escherichia coli. Minimum inhibitory concentration and minimum bactericidal concentration of the extracts ranged 1.563.125 and 3.125-12.5 mg ml-1 for Staphylococcus aureus, respectively. Based on the findings, Iranian date seeds are good sources of extractable phenolic compounds with notable antioxidant activities, which can be used as natural additives in formulations of various products such as functional foods and dietary supplements. Furthermore, these seeds can be converted to value added products through biotechnological processes. Conflict of interest: The authors declare no conflict of interest.